Penerapan Affirmative Action oleh Partai Politik sebagai Upaya Peningkatan Keterwakilan Perempuan pada Lembaga Legislatif - Listiyani, Angela Ranina; Maharani, Andina Elok Puri (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis study aims to examine the application of affirmative action by political parties in an effort to increase women’s representation in the legislative body. The research method used is empirical juridical that is in addition to being reviewed through legislation, it is also examined about the legal facts in the field. The type of data collected includes primary and secondary legal materials. Data collection techniques are by library research, interviews, and observations. Meanwhile the data analysis technique used is the deduction method. The objects of this study were Surakarta City PDIP, Surakarta City Golkar Party, and Surakarta City PSI. From this study, it was produced that (1) Surakarta City PDIP, Surakarta City Golkar Party, and Surakarta City PSI were still less than optimal in implementing Affirmative Action to increase women’s participation in legislative institutions because of the AD ART Political Parties, work programs, political culture, and the participation of women in regional elections is still lacking. (2) the lack of political parties in implementing Affirmative Action to increase women’s participation cannot be separated from gender injustice, namely subordination, which considers male gender more capacity to be involved in politics than female gender, causing male superiority and female cadre’s lack of confidence, a double burden namely the view of the community that if women want to do politics then all forms of household affairs must continue to be carried out like being a housewife, and marginalization of women who politicize both in the internal domain of political parties and in the external domain that places women at the periphery in the sense of prioritizing all the interests of female cadres.Keywords: affirmative action; political parties; women in the legislature.